IDENTIFIKASI JENIS BATUAN CANDI DUKUH, CANDI NGEMPON DAN CANDI GEDONG SONGO MENGGUNAKAN SONIC VIEWER-SX 5251 - Pertiwi Pertiwi; Tony Yulianto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
Rock identification with rock mechanics properties of rock samples to determine the type of Dukuh temple , Ngempon temple and Gedong songo temple, with the ultrasonic wave method using Sonic Viewer SX - 5251. Travel time of ultrasonic waves on the sample is used to obtain S and P wave velocity. Data has processing using Excel software. Value of the S and P wave velocity, shear modulus , rock elasticity , and Poisson 's Ratio will be correlated with rock density tables, P and S wave velocity tables and rock mechanics properties table it can be seen kind of rock from each of the rock physics properties. The research result shows that rock composite Ngempon temple, Dukuh temple , and Gedong Songo are Andesite. In addition to the density values which obtained, the level of rocks weathering can be defermind as well. Dukuh B rock sample with a density of 2.66 gm /cm3 can be classified in level I, it show that those rocks are strong and good. On the other samples of the Ngempon temple, gedong Songo or from another Dukuh the density values which obtained are from 2.33 to 2.49 can be classified at level II or it can be said to be strong enough .Key Word : Ultrasonic Wave, Sonic Viewer, Ngempon Temple, Dukuh Temple, Gedong Songo Temple, Weathering, and Andesite Rocks.